Balancing long-term health literacy skills development with immediate action to facilitate use of reliable health information on COVID-19 in England (Journal of EAHIL, 2021)
High-quality healthcare information exists for patients and the public, but a high proportion of individuals do not have the skills to access, assess and use this information. Health Education England leads the strategic development of knowledge and library services in the National Health Service (NHS) in England. One of the goals of the Knowledge for Healthcare strategy is that staff, learners, patients and the public are better equipped to use evidence-based patient, health and wellbeing information for shared decision-making and self-care. This paper outlines a partnership approach to raising awareness of health literacy, and improving the health literacy awareness and skills of NHS staff and citizens, whilst meeting immediate needs to access trustworthy information on COVID-19.